ALÉM DA PRIMEIRA VISTA: PROPOSTAS METODOLÓGICAS PARA A ANÁLISE FOTOGRÁFICA NO CONTEXTO COLONIAL MOÇAMBICANO - Leandro Antonio Guirro (Universidade do Oeste Paulista, 2015)
The sources are still obstacles to researchers interested in the history of Africa. Thus, the work that follows its main purpose contributing to the development of alternatives that facilitate research about the African continent. For this purpose, it is methodological proposals (developed by Kossoy, Benjamin Burke, Meneses, Mauad and Paiva) that allow understand the Photo Albums and Descriptions of the Colony of Mozambique, produced by Portuguese colonists in the late 1920s. It pointes that the photographic act consists of several elements, meanings and intentions that should be questioned by those who analyze the images. It concludes that the exposed interpretations make relevant data for the study of photographic documents, linked or not with African theme.